A randomized controlled study of autogenous platelet-rich gel and standard therapy in the treatment of diabetic refractory skin ulcer - J. Alfeehan, Mohammed; Asaad Mahmood, Luay; Ismael Abdulelah, Salah (International Journal of Psychosocial Rehabilitation, 2020)
Objective To evaluate the efficacy and safety of autogenous platelet-rich gel (APG) in the treatment of diabetic refractory skin ulcers. Methods from April 2017 to February 2018, 56 patients with diabetic skin ulcers hospitalized in our department were randomly divided into APG treatment (23 cases) and standard treatment group (33 cases). Both groups of patients used insulin to control blood sugar, strictly control the orbit and blood lipids, and were given anti-blood plates, improved microcirculation, anti-infection and other general treatments and standard treatment of local ulcer wounds. Patients in the APG treatment group used self-made APG and applied wound dressing according to the wound volume / area; the standard treatment group applied wound dressing directly. The course of treatment is until the wound is healed, a flap transplant is performed, or it is over 12 weeks. Results All patients except the standard treatment group were lost to follow-up. The ulcer healing rate in the APG group was 22/23 (95.7%) and the total effective rate was 100%; the ulcer healing rate in the standard treatment group was 23/33 (69.6%) and the total effective rate was 72.1% The difference between the two groups was statistically significant (P values were o.002 and O.009, respectively); analysis of the healing curve and sinus closure curve during Meier ulcer in Kaplan Meier analysis P